Oświeceniowe racjonalności - Drozdowicz, Zbigniew (My University, 2015)
One of the leading motives of the Enlightenment era was the motive of reason, reasonability and rationality. The problem is that it was and is approached and presented in different ways; however some of these approaches and presentations are complementary, while others are contradictory, and some are complementary from a certain point of view and contradictory from another. In my considerations I present several of those ways of approaching and presenting reason, reasonability and rationality. I recall here both the direct creators of this era (such as I. Kant, D. Diderot and A. Smith), as well outside observers and researchers (such as M. Weber and Ch. Taylor).
Keywords: enlighten reason; reasonability; rationality; homo oeconomicus; secularization